2016
DOI: 10.1007/s10926-016-9651-4
|View full text |Cite
|
Sign up to set email alerts
|

Return to Work 2–5 Years After Stroke: A Cross Sectional Study in a Hospital-Based Population

Abstract: Purpose To describe factors associated with RTW in patients 2-5 years after stroke. Methods Cross sectional study, including patients 2-5 years after hospitalization for a first-ever stroke, who were <65 years and had been gainfully employed before stroke. Patients completed a set of questionnaires on working status and educational level, physical functioning (Frenchay Activities Index, FAI), mental functioning (Hospital Anxiety and Depression Scale, HADS), Coping Orientations to Problems Experienced, (COPE ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 39 publications
7
36
0
Order By: Relevance
“…(2017) a, g Iakova et al (2012)Karoly et al (2013) d Norlund et al (2011)Strober and Arnett (2016) a Arwert et al (2017) a Dawson et al (2011) a, d De Vries et al . (2012b) Grytten et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2017) a, g Iakova et al (2012)Karoly et al (2013) d Norlund et al (2011)Strober and Arnett (2016) a Arwert et al (2017) a Dawson et al (2011) a, d De Vries et al . (2012b) Grytten et al .…”
Section: Resultsmentioning
confidence: 99%
“…In total, 14 quantitative studies investigated the association between different coping strategies and work participation (Table 2: Arwert et al 2017; Dawson et al 2011; De Vries et al 2012b; Grytten et al 2017; Heymans et al 2009; Huijs et al 2012; Iakova et al 2012; Karoly et al 2013; Luk et al 2010; Norlund et al 2011; Øyeflaten et al 2008, 2016; Strober and Arnett 2016; Truchon et al 2010). Nine studies found an effect of some coping strategies (Arwert et al 2017; Dawson et al 2011; Grytten et al 2017; Huijs et al 2012; Iakova et al 2012; Karoly et al 2013; Norlund et al 2011; Øyeflaten et al 2008; Strober and Arnett 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For others the symptoms can be more "hidden" as cognitive and emotional changes as well as fatigue [4] and symptoms related to seeing and speech [5]. A major consequence of stroke is work disability [6]. Fewer than half of those who were working at the time of their stroke return to work (RTW) [7], thus approximately 3,000 Swedish workers do not return to work annually due to their stroke [2].…”
Section: Introductionmentioning
confidence: 99%
“…Physical impairment (3) as well as reduced cognitive function such as fatigue, memory and concentration problems are common, affecting the patient's functioning in everyday life (4,5). With reduced cognitive function, it becomes harder to manage social life, living independently (6,7), getting a job or returning to work (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%